Secondary Metabolite Test of Heterotrophic Bacteria from Sea Water in Sungai Kayu Ara Village Against Pathogenic Bacteria - Y Hutasoit, Anjeli; Feliatra, Feliatra; Dahliaty, Andy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted from April - July 2018 at the Laboratory of Organic Chemistry and Natural Materials Synthesis Research, Faculty of Mathematics and Natural Sciences and Marine Microbiology Laboratory in the Department of Marine Sciences, Faculty of Fisheries and Marine Sciences, University of Riau. The purpose of this research is to know the ability of secondary metabolites to inhibit heterotrophic bacteria in inhibiting the activity of pathogenic bacteria (Vibrioalginolyticus, Aeromonas hydrophila and Pseudomonas aeruginosa). The research method used is the experimental method. 10 isolates of heterotrophic bacteria were obtained from a collection of Marine Microbiology, Faculty of Fisheries and Marine laboratories which were able to produce secondary metabolites. Each bacterial isolate was tested on pathogenic bacteria, namely Aeromonashydrophila (P), Pseudomonas aeruginosa (Q), Vibrio alginolyticus (R) using paper discs and each isolate was carried out 3 repetitions, so that 90 experiments were obtained. Test results of secondary metabolites of 10 heterotrophic bacterial isolates have the ability to inhibit the growth of pathogenic bacteria. The best isolate is J isolates with clear zones formed wider than the other test bacteria which is 12,35 mm and the activity of the bacteria was 1877,78 mm2 / ml. This inhibitory power is caused by the presence of compounds that are anti-microbial namely secondary metabolites. Isolates A, D, F, G, H are resistant to pathogenic bacteria Aeromonas hydrophilla, isolates D, E, G, J are resistant to pathogenic bacteria Pseudomonas aeruginosa. This is indicated by the presence of a cloudy zone around the disc paper that is formed during the inhibitory test Keyword : Secondary Metabolites, Heterotrophic Bacteria, Inhibitory Power